The presence of ASXL1 mutations as well as a total number of myeloid driver mutations higher than two is strongly associated with the diagnosis of primary myelofibrosis as opposed to essential thrombocythemia - Campregher, Paulo Vidal (2014)
Hosp Israelita Albert Einstein, Sao Paulo, Brazil